Decoding the Great Pyramid [videorecording (DVD)] - Douglas, Michael, 1944-; Meyers, Eric, 1959- (PBS Distribution, 2019)
How did the Egyptians engineer the Great Pyramid of Giza so precisely, and who were the thousands of laborers who raised the stones? New archaeological evidence, including a logbook of a labor team leader, provides new insights into these age-old questions. Nova delves into these construction secrets to trace how mobilizing labor and resources on such a massive scale transformed ancient Egypt.